Increasing Samosir Red Onion (Allium ascalonicum L.) Production Through Induction of Ethyl Methane Sulfonate (EMS) Mutation and Administration Interval of Silver Nanoparticles Natural PGR (AGNPS-A) - Waruwu, Marinus Mintodeus; Saragih, Wismaroh Sanniwati; Oesman, Roswita (Central Research Institute For Agriculture, 2024)
Samosir Shallots (Allium ascalonicum L.) is one of the vegetable commodities that is widely used by people as a food flavoring ingredient. Apart from being a flavoring, shallots are also widely used as traditional medicine. The importance of applying Ethyl Methane Sulfonate (EMS) mutation technology and providing natural ZPT silver nanoparticles (AGNPS-A) on the growth and productivity of Samosir shallots. This research was carried out from May to August 2023, which took place in the experimental garden of the Faculty of Agriculture, Indonesian Community Development University (UPMI) Jl. Balai Desa Pasar 12 Marindal II Medan Amplas. This research used a Completely Randomized Design (CRD)which consists of 3 factors with levels of 3x3x2. First factor, AGNPS-A administration interval (A), A0 (Control); A1 (3 MST); A2 (5 MST). Second factor, Ethyl Methane Sulfonate (E),E0 (Control); E1 (0.25%); E2 (0.5%); Factor (iii), Soaking time (J), J1 (2 hours); J2 (4 Hours). The results of EMS and AGNPS-A treatment had a very real influence in increasing onion production on the observation parameters of plant height, number of leaves, number of tillers and wet weight. This combination of treatments is able to interact to increase the production of Samosir shallots(Allium ascalonicum L.).